2021
DOI: 10.3171/2020.6.spine20171
|View full text |Cite
|
Sign up to set email alerts
|

A single-center retrospective analysis of 3- or 4-level anterior cervical discectomy and fusion: surgical outcomes in 66 patients

Abstract: OBJECTIVEAnterior cervical discectomy and fusion (ACDF) is a safe and effective intervention to treat cervical spine pathology. Although these were originally performed as single-level procedures, multilevel ACDF has been performed for patients with extensive degenerative disc disease. To date, there is a paucity of data regarding outcomes related to ACDFs of 3 or more levels. The purpose of this study was to compare surgical outcomes of 3- and 4-level ACDF procedures.METHODSThe authors performed a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…For ACDF, fewer level cases are the most common [12] , but four-level cases account for approximately 2.4% of such cases [12] . Regarding treatment for multi-level cervical pathology, four-level ACDF and PCF have been compared with small sample sizes studies [ 8 , 10 , [13] , [14] , [15] ]. Zhai et al evaluated 19 patients that underwent four-level ACDF and 25 that underwent four-level PCF and found similar clinical and radiographical outcomes, though the small sample size limited their ability to control for confounders and obtain adequate power for outcome comparison [10] .…”
Section: Introductionmentioning
confidence: 99%
“…For ACDF, fewer level cases are the most common [12] , but four-level cases account for approximately 2.4% of such cases [12] . Regarding treatment for multi-level cervical pathology, four-level ACDF and PCF have been compared with small sample sizes studies [ 8 , 10 , [13] , [14] , [15] ]. Zhai et al evaluated 19 patients that underwent four-level ACDF and 25 that underwent four-level PCF and found similar clinical and radiographical outcomes, though the small sample size limited their ability to control for confounders and obtain adequate power for outcome comparison [10] .…”
Section: Introductionmentioning
confidence: 99%
“…In 71 patients undergoing 3-level ACDF and 26 patients with 4-level ACDF, fusion rates were 94.4% and 84.6%, respectively, with an average follow-up of 7.6 years. 28 McClure et al 29 studied patients undergoing 3-level and 4-level ACDFs and found significantly lower fusions rates at more caudal levels, and fusion rates were similar between the 3-level and 4-level groups. However, revision rates were required in 6.4% of 3-level patients and 16.0% of patients undergoing 4-level surgery, emphasizing the increased risk of suboptimal outcomes in 4-level operations.…”
Section: Anterior Proceduresmentioning
confidence: 99%
“…Exclusion criteria: (1) Preoperative dysphagia; (2) A history of other disorders that may trigger symptoms of dysphagia, such as craniocerebral trauma or cerebral infarction; (3) Received revision surgery; (4) Combined with cervical deformity, tumor, severe osteoporosis, ankylosing spondylitis and rheumatoid arthritis; (5) Incomplete imaging data; (6) loss of follow-up or follow-up was less than 1 year; (7) Received hybrid surgery.…”
Section: Inclusion and Exclusion Criteria Of Patientsmentioning
confidence: 99%
“…Anterior cervical discectomy and fusion (ACDF) is the gold standard for the treatment of cervical spondylosis. [1][2][3][4] Anterior cage-plate construct is commonly used in ACDF in order to enhance segmental stability improve cervical sagittal alignment, reduce graft extrusion and subsidence, and increase fusion rates. These techniques have their own bene ts as well as potential drawbacks and adverse effects.…”
Section: Introductionmentioning
confidence: 99%